The reciprocal relationship between mathematics self-efficacy and mathematics performance in US high school students: Instrumental variables estimates and gender differences - Sakellariou, Chris (Frontiers in Psychology, 2022)
Background: I investigated the reciprocal relationship between self-efficacy and achievement in the domain of mathematics for high school students in the US, using HSLS:2009 and first follow-up longitudinal survey data with measurements at a 2.5-year interval. Methods: Within gender, Instrumental Variables (IV) regressions were estimated, to derive causal effect estimates of earlier math self-efficacy on later math achievement and vice versa. Particular attention was paid to the validity of instruments used. The objective is to account for unobserved heterogeneity and uncover gender differences in effects. Results: Evidence of robust reciprocal effects between self-efficacy and achievement for male students is presented, with the dominant effect from earlier achievement to later self-efficacy. For girls, such effects if present, are weaker. Generally, IV estimates are higher than OLS estimates for males, but not for females. As opposed to earlier correlational studies which did not find significant gender differences despite theoretical expectations for their existence, I document higher effects for male students. Discussion: Possibly involved in the heterogeneity of findings by estimation method and gender is misreporting of self-efficacy and/or faulty recollection of past mathematics performance, and gender differences thereof. Given that girls report lower math self-efficacy than boys, while actual performance in mathematics does not differ significantly between genders, increasing girls’ positivity bias in mathematics through feedback from teachers on their individual/group good past math performances, toward bringing their perceptions into line with past achievements, is a promising intervention.